Methods and Tools for Forecasting in a Commercial Bank (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
In an unstable macroeconomic environment, commercial banks face the need to use effective forecasting methods. This paper examines macroeconomic forecasting, econometric models, and digital technologies that help commercial banks minimize risks and enhance the efficiency of strategic management. Particular attention is given to the analysis of modern forecasting tools in banking activities.